Kronični periapikalni parodontitis - Ihan Hren, Nataša (Medicinski razgledi, 2000)
Chronical periapical parodontitis is chronical inflamatory response of periapical parodontal tissues to bacterial infection. Patohistologically it represents nonspecifical chronical mononuclear inflamatory infiltration of fibrous tissue. Its pathogenesis depends on more factors. The immunological mechanisms have important rule, among them expecially late hypersensitivity.
Keywords: obzobno tkivo; Periapical periodontitis; parodontalne bolezni; Pathology; vnetja; Microbiology; Immunology; Chronic disease